Approaches to Integrating Entrepreneurial Education in School Curriculum - Mpuangnan, Kofi Nkonkonya; Govender, Samantha; Mhlongo, Hlegiwe Romualda (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2024)
In recent years, a noticeable and worrisome pattern has emerged in numerous developing nations which is a steady and persistent rise in unemployment rates. To effectively tackle this pressing unemployment issue, it is imperative to adopt a holistic approach like incorporating entrepreneurial education across curriculum at all levels of the educational system. Therefore, the authors explored approaches to integrating entrepreneurial education into school curricula focusing on the following research questions. How can an entrepreneurial mindset among learners be promoted in school? And how far have pedagogical approaches improved entrepreneurship in schools? To address these questions, a systematic literature review underpinned by Human Capital Theory. The data were specifically sought from publishers with wide coverage of scholarly literature like Sage, Taylor and Francis, Emirate, and Springer, covering publications from 1965 to 2023. The search was supported by two broad terms such as promoting entrepreneurial mindset in learners and pedagogical strategies for enhancing entrepreneurship. It was found that an entrepreneurial mindset could be acquired through an innovative classroom environment, resilience, and guest speakers. Also, teachers could promote entrepreneurial education through the adoption of pedagogical approaches such as hands-on learning and experiential activities, role-playing, and business simulation games. It was recommended that the Ministry of Education should develop tailored training programs and workshops aimed at empowering educators with the essential competencies and insights to deliver impactful entrepreneurial education.